What Are Constructions, and What Else Is Out There? An Associationist Perspective - Kapatsinski, Vsevolod (Frontiers in Communication, 2021)
This paper argues that constructions are emergent networks of associations connecting meanings to forms and forms to each other. Settling on a new form is a complex process that involves meanings and forms clamoring for themselves and their associates to be incorporated into the production plan being constructed. Morphological evidence for productive arbitrary paradigmatic mappings suggests that in some languages constructions co-exist with second-order schemas and even conditioned operations (rules). However, negative associations between forms and meanings can extend the power of constructions-only approaches to account for such patterns. This paper discusses whether each kind of association forming the constructicon is bidirectional or unidirectional, and how it might be learned, and exemplifies the interaction between schematic and paradigmatic associations using a previously undescribed adjectival construction in Russian.